Child Abuse in a Changing Environment: A Legal Study - Reena Rani Jat (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2021)
Humans have made a lot of progress in the changing environment and in the race to prove themselves to be the best, and have also changed the way they work. Due to which time is saved and if machines are used to do the work, then good quality producers are also made. Now if we look at education, then education has moved from the ashrams of Gurukuls to schools, colleges and universities. Due to this education has also turned towards professionalism. In today's era, many miracles of science have been seen, which have turned human civilization towards a new dimension and oriented us toward new goals. Now if we look at other aspects, then as much progress has been made due to the above-mentioned resources, new methods of crimes have also arisen. In which child abuse is also prominent. Through this research paper, by doing a legal study of child abuse in the changing environment, to know the causes of these crimes and discuss about the measures to prevent those crimes.